2015
DOI: 10.1007/s40615-015-0198-4
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Dance Program Improves Hypertension Management for Native Hawaiians and Pacific Islanders: a Pilot Randomized Trial

Abstract: ObjectiveNative Hawaiians and Pacific Islanders (NHPI) bear an unequal burden of hypertension and cardiovascular disease. Hula, the traditional dance of Hawaii, has shown to be a culturally meaningful form of moderate-vigorous physical activity for NHPI. A pilot study was done in Honolulu, Hawaii, to test a 12-week hula-based intervention, coupled with self-care education, on blood pressure management in NHPI with hypertension in 2013.MethodNHPI with a systolic blood pressure (SBP) ≥140 mmHg were randomized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 44 publications
4
91
0
Order By: Relevance
“…On the other hand, there are few data on the potential impact of culturally designed versus non-adapted (i.e., general audience) interventions (Belone et al, 2017; Belone et al, 2016; Kaholokula et al, 2017). Most of the studies reviewed here are outside the scope of addressing such questions but the IRINAH-developed interventions could be tested in future trials examining this issue.…”
Section: Honoring the Medicine (Discussion)mentioning
confidence: 99%
“…On the other hand, there are few data on the potential impact of culturally designed versus non-adapted (i.e., general audience) interventions (Belone et al, 2017; Belone et al, 2016; Kaholokula et al, 2017). Most of the studies reviewed here are outside the scope of addressing such questions but the IRINAH-developed interventions could be tested in future trials examining this issue.…”
Section: Honoring the Medicine (Discussion)mentioning
confidence: 99%
“…A systematic review conducted on the overall health benefits of Zumba reported that it enhanced aerobic and cardiovascular outcomes such as weight loss (1-3.6% reduction), body mass index (BMI) (1.1-3.7%), and waist circumference (3.5-4%) in participants within programs that lasted 8-40 weeks [47]. To that end, one can also argue that Zumba may help reduce more common barriers that Filipinos face to engaging in PA, since it includes a strong cultural component that can enhance activity among ethnic populations, especially when it is tailored to a specific culture [29]. Additionally, it is important to note that dance, which includes Zumba, was reported as the second most common leisure PA among women of older age [48].…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that incorporate culturally relevant and tailored strategies to increase PA and healthy lifestyle behaviors have shown promising outcomes for promoting health among ethnic minorities [29][30][31][32][33]. The impact of a culturally appropriate PA intervention on health and physical outcomes has not been previously studied in Filipino Americans.…”
mentioning
confidence: 99%
“…Quality control checks and calibration for equipment and measurements were conducted regularly. Physical functioning capacity was assessed using a 6‐minute walk test (6MWT) with participants requested to walk briskly in a marked lap distance over 6 minutes . Participants could rest if needed and resume walking once able; however, the timer was not stopped during the rest period.…”
Section: Methodsmentioning
confidence: 99%